ASSOCIATION BETWEEN CARDIOVASCULAR RISK AND QUALITY OF LIFE IN INDUSTRIAL SECTOR WORKERS (CIPEEX, 2026)
Introduction: In the industrial sector, precarious conditions, occupational risks, long working hours, and inflexible schedules generate stress, fatigue, and health impairments, negatively impacting quality of life (QoL). Metabolic alterations, such as elevated blood glucose, triglycerides, and LDL-C, along with reduced HDL-C, are associated with occupational stress, while the integrated relationship with the QoL of industrial workers has been little explored. Objective: To analyze the influence of metabolic risk on the quality of life of industrial sector workers. Method: Cross-sectional study with 141 industrial workers in Anápolis. The following markers were measured or calculated: body mass index, lipid profile, blood glucose, and quality of life using the SF-36 questionnaire. Results: WC (p
Keywords: Quality of Life; Metabolic Stress; Industry; Workers